EFFECT OF TRICHODERMA HARIZANUM TO CONTROL DAMPING OFF DISEASE AND GROWTH PROMOTION IN CHILLI (CAPSICUM ANNUUM ) - SUBASH, N; MEENAKSHISUNDARAM, M; UNNAMALAI, N; SASIKUMAR, C (International Journal of Pharma and Bio Sciences, 2013)
Chilli is one of the important spices and cultivated around the world for its peculiar hot taste. Chilli crops prone to affect by seedling disease called damping off. In order to overcome this problem, efforts have been made to evaluate the efficiency of the biocontrol agent Trichoderma harizanum for controlling the damping off disease in chilli. T. harizanum was isolated from the garden soil and identified through microscopic and recommended standard methods. The antagonistic activity of the T. harizanum was evaluated against the pathogenic fungi responsible for damping disease i.e., Fusarium oxysporium, Rhizoctonia solani and Alternaria alternata proved the efficiency to inhibit the growth of all the above pathogens. The T. harizanum was formulated with talcum powder and applied as foliar spray on damping off diseased chilli plants. After 49 days of treatment, T. harizanum treated chilli plants showed more plant height (75 %), number of leaves (60 %), buds (10 %) and fruits (6 %) than control. Hence we concluded that, T. harizanum can be recommended not only for the control of damping off disease in chilli plants and also to enhance the growth of the plants.